High‐Efficiency Narrowband Multi‐Resonance Emitter Fusing Indolocarbazole Donors for BT. 2020 Red Electroluminescence and Ultralong Operation Lifetime - Fan, Tianjiao; Du, MingXu; Jia, Xiaoqin; Wang, Lu; Yin, Zheng; Shu, Yilin; Zhang, Yuewei; Wei, Jinbei; Zhang, Dongdong; Duan, Lian (Advanced materials (Weinheim), 2023)
Polycyclic heteroaromatics with multi‐resonance (MR) characteristics are attractive materials for narrowband emitters in wide‐color‐gamut organic light‐emitting diodes. However, MR emitters with pure‐red colors are still rare and usually exhibit problematic spectral broadening when redshifting emission. Here, a narrowband pure‐red MR emitter is reported by fusing indolocarbazole segments into a boron/oxygen‐embedded skeleton, realizing BT.2020 red electroluminescence for the first time together with a high efficiency and an ultralong lifetime. The rigid indolocarbazole segment possesses a strong electron‐donating ability due to its para‐positioned nitrogen–π–nitrogen backbone and also enlarges the π‐extension of the MR skeleton to suppress structural displacement during radiation, achieving concurrently redshifted and narrowed emission spectrum. An emission maximum at 637 nm with a full width at half‐maxima of merely 32 nm (0.097 eV) is recorded in toluene. The corresponding device simultaneously exhibits CIE coordinates of (0.708, 0.292) precisely matching the BT.2020 red point, a high external quantum efficiency of 34.4% with low roll‐off and an ultralong LT95 (time to 95% of the initial luminance) of >10 000 h at 1000 cd m−2. These performance characteristics are superior even to those of state‐of‐the‐art perovskite and quantum‐dot‐based devices for this specific color, paving the way toward practical applications. A pure‐red multi‐resonance emitter fused with indolocarbazole segments is developed, simultaneously redshifting and narrowing the emission color. The corresponding organic light‐emitting diode realizes BT.2020 red coordinates of (0.708, 0.292), also achieving an impressive maximum external quantum efficiency of 34.4% and an ultralong LT95 of over 10 000 h at an initial luminance of 1000 cd m−2.